Computer Applications for Bio-technology, Multimedia, and Ubiquitous City International Conferences MulGraB, BSBT and IUrC 2012 Held as Part of the Future Generation Information Technology Conference, FGIT 2012, Gangneug, Korea, December 16-19, 2012. Proceedings - Kim, Tai-hoon.; Kang, Jeong-Jin.; Grosky, William I.; Arslan, Tughrul; Pissinou, Niki.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This volume constitutes the refereed proceedings of the International Conferences, BSBT, MulGraB and IUrC 2012, held as part of the Future Generation Information Technology Conference, FGIT 2012, Gangneung, Korea, in December 2012. The papers presented were carefully reviewed and selected from numerous submissions and focus on the various aspects of multimedia, computer graphics and broadcasting, bio-science and bio-technology, and intelligent urban computing.
Multimedia -- Computer graphics -- Broadcasting -- Bio-science and bio-technology -- Intelligent urban computing.
Keywords: Computer science; Computer communication systems; Data encryption (Computer science).; Algorithms; Artificial intelligence; Management information systems; Computer Science; Computer Communication Networks; Information Systems Applications (incl. Internet).; Artificial Intelligence (incl. Robotics).; Algorithm Analysis and Problem Complexity; Management of Computing and Information Systems; Data Encryption; Electronic books